PERENCANAAN PENYUSUNAN RENCANA KERJA PEMERINTAH DAERAH KOTA DUMAI TAHUN 2018 - Sasa Fitarda; Baskoro Wicaksono (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
Planning is an important key to starting a program. When Planning, choices are made, steps are arranged to guide so that the will can be grasped at the time that has been outlined such as the preparation of the local government work plan. Planning is defined as the process of setting goals and determining the choice of actions taken, and deciding steps to achieve goals. A plan is a statement that is needed and must be executed so that the goal is reached. The formulation of the problem in this research is how the preparation of the Dumai city regional government work plan what are the factors that cause the dynamics in the preparation of the Dumai city regional government work plan. The purpose of this study is to describe the preparation of the Dumai city regional government work plan and describe the factors that cause in the preparation of the Dumai city regional government work plan. The research method used is a qualitative method with a descriptive approach. Using data collection techniques from interviews, observations, and RKPD documents in Dumai city.Keywords : Planning, Local Government Work Plan, Bureaucratic.